Percepción De Factores Que Influyen En La Presencia De Embarazos En Las Adolescentes Menores De 15 Años De Dibulla, La Guajira (2023)
The present investigation focuses on identifying the perception of pregnant adolescents under 15 years of age regarding the factors that influenced the presence of pregnancies at an early age in the municipal seat-Dibulla, La Guajira; a population particularly vulnerable to unplanned pregnancies. The objective of this study is to identify the sociocultural, family and socioeconomic factors perceived in the presence of these pregnancies. To carry out this analysis, a qualitative methodology based on semi-structured interviews was used. To represent the target population, a representative sample of four pregnant adolescents, aged between 13 and 15 years, was selected. In relation to the results obtained, it was identified that family factors such as parental abandonment and influence by the partner, significantly affect the presence of unplanned pregnancies in adolescents. On the other hand, the perceived sociocultural factors were school dropout and also the influence of the partner. Additionally, socioeconomic factors such as precarious living conditions, variable economic income and low economic income, were also identified as determinants that increase the probability of having unwanted pregnancies. Based on these results, it is necessary to implement prevention campaigns that address sexual education and the importance of contraceptive methods. These campaigns must be carried out in conjunction with the corresponding institutions and must be aimed at adolescents and their families. It is essential to promote communication and dialogue in homes to prevent unwanted pregnancies and ensure a healthy and full life for young people